Reactivated faulting near Cushing, Oklahoma: Increased potential for a triggered earthquake in an area of United States strategic infrastructure. Issue 20 (23rd October 2015) - McNamara, D. E.; Hayes, G. P.; Benz, H. M.; Williams, R. A.; McMahon, N. D.; Aster, R. C.; Holland, A.; Sickbert, T.; Herrmann, R.; Briggs, R.; Smoczyk, G.; Bergman, E.; et al.
Abstract: In October 2014 two moderate‐sized earthquakes ( Mw 4.0 and 4.3) struck south of Cushing, Oklahoma, below the largest crude oil storage facility in the world. Combined analysis of the spatial distribution of earthquakes and regional moment tensor focal mechanisms indicate reactivation of a subsurface unnamed and unmapped left‐lateral strike‐slip fault. Coulomb failure stress change calculations using the relocated seismicity and slip distribution determined from regional moment tensors, allow for the possibility that the Wilzetta‐Whitetail fault zone south of Cushing, Oklahoma, could produce a large, damaging earthquake comparable to the 2011 Prague event. Resultant very strong shaking levels (MMI VII) in the epicentral region present the possibility of this potential earthquake causing moderate to heavy damage to national strategic infrastructure and local communities. Key Points: Cushing earthquakes have transferred stress to faults capable of producing larger earthquakes Increased earthquake hazard exists for energy industry infrastructure near Cushing Oklahoma The Cushing sequence is likely related to wastewater injection